KOMUNIKASI KELUARGA UNTUK MEMOTIVASI TANGGUNG JAWAB ANAK BELAJAR DI MASA PANDEMI - Ghozi Garbo Sumarsono; Agus Naryoso (Interaksi Online, 2022)
The emergence of the COVID-19 pandemic has changed all aspects of Indonesian people's lives, one of which is education. This change began to be felt since the implementation of the "Work From Home" activity policy, which changed educational activities to the Pembelajaran Jarak Jauh (PJJ). However, this has an impact on children's laziness levels, as a result of boredom, monotonous activities, and lack of face-to-face socialization. In distance learning activities, children certainly need support from their families in motivating them to learn. Judging from this phenomenon, researchers have an interest in knowing how to communicate within the family to motivate children's studying responsibilities during a pandemic. This study uses a qualitative approach and phenomenological methods. The study population was taken from families who have school children at the junior high and high school levels who were affected by the corona pandemic. From this population, a sample of 6 informants was taken consisting of 3 parents and 3 students. In collecting data, this study used in-depth interviews, so that saturated and detailed data were obtained. In addition, there are secondary data sources such as literature studies and the latest information from trusted online media portals. The data is then analyzed through the stages of horizontalization, textural description, structural description, and describe the existing phenomena. This study produces data that (1) the combination of pluralistic and consensual family communication patterns builds children's sense of responsibility for studying; (2) the combination of pluralism and consensual communication patterns as well as democratic parenting can create a good learning environment for children during this pandemic; (3) democratic parenting provides a comfortable learning environment for children so that they can motivate children to learn.